2021
DOI: 10.1021/acs.iecr.1c03671
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Heat Duty of MEA Regeneration Using a Sulfonic Acid-Functionalized Mesoporous MCM-41 Catalyst

Abstract: Amine-based CO 2 capture is a promising method to limit global CO 2 emissions. However, large thermal energy consumption for CO 2 desorption during amine regeneration has limited large-scale worldwide applications. Here, we show that an efficient MCM-41-SO 3 H-0.6 catalyst presented a superior catalytic performance, decreasing the relative heat duty by one-third and enhancing the instantaneous desorption rate by up to 195% in comparison with the monoethanolamine (MEA) regeneration without catalysts. The excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Compared with the blended amine, biphasic amine, and ionic liquid that exhibit higher reaction kinetics while also higher volatility, corrosivity, and viscosity, the enhanced desorption rates by SACs enable a reduction of CO 2 desorption temperature and allow the conventional regeneration process to operate at temperatures below 100 °C, which could minimize evaporation energy consumption and prevent MEA degradation. , However, the effectiveness of such SACs is limited by their poor specific surface area, pore structure, and durability under treatment with aqueous amine solutions. , The three-dimensional hydrophobic surface with small micropore size distribution of the SACs restricts the diffusion of polar reactants (RNHCOO – , RNH 3 + , and H 3 O + ) in their to approach active sites . The active protonated sites of BASs are prone to leach in an alkaline environment, and the metal species of LASs will rapidly aggregate with −NH 2 groups and be removed from activity, thus leading to the deactivation of the SACs . Therefore, although amine regeneration using these SACs can increase the energy efficiency, the inaccessibility and deactivation of the active sites must be suppressed to further promote energy-efficient amine regeneration processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the blended amine, biphasic amine, and ionic liquid that exhibit higher reaction kinetics while also higher volatility, corrosivity, and viscosity, the enhanced desorption rates by SACs enable a reduction of CO 2 desorption temperature and allow the conventional regeneration process to operate at temperatures below 100 °C, which could minimize evaporation energy consumption and prevent MEA degradation. , However, the effectiveness of such SACs is limited by their poor specific surface area, pore structure, and durability under treatment with aqueous amine solutions. , The three-dimensional hydrophobic surface with small micropore size distribution of the SACs restricts the diffusion of polar reactants (RNHCOO – , RNH 3 + , and H 3 O + ) in their to approach active sites . The active protonated sites of BASs are prone to leach in an alkaline environment, and the metal species of LASs will rapidly aggregate with −NH 2 groups and be removed from activity, thus leading to the deactivation of the SACs . Therefore, although amine regeneration using these SACs can increase the energy efficiency, the inaccessibility and deactivation of the active sites must be suppressed to further promote energy-efficient amine regeneration processes.…”
Section: Introductionmentioning
confidence: 99%
“…26 The active protonated sites of BASs are prone to leach in an alkaline environment, and the metal species of LASs will rapidly aggregate with −NH 2 groups and be removed from activity, thus leading to the deactivation of the SACs. 27 Therefore, although amine regeneration using these SACs can increase the energy efficiency, the inaccessibility and deactivation of the active sites must be suppressed to further promote energy-efficient amine regeneration processes. Furthermore, the lowered regeneration temperature is still too high to minimize indirect CO 2 emissions due to the usage of fuels to reach the required temperature, hence there are no benefits to achieving Net Zero.…”
Section: Introductionmentioning
confidence: 99%
“…As for acid capacity, note that the Amberlyst-15, Amberlite-732, and Amberlyst-35 catalysts displayed similar quantities of acid sites between 3.13 and 3.41 mmol H + /g cat , while the Amberlite IR-120 catalyst possessed the lowest acid capacity at 2.29 mmol H + /g cat . A previous study reported 43 that the mesoporous surface area and acid sites have a positive effect on catalytic performance, because the large surface area enhances the active sites and the acid sites accelerate proton transfer. Therefore, the excellent catalytic performance of Amberlyst-15 can be attributed to the combined effect of the mesoporous surface area and acid capacity.…”
Section: Resultsmentioning
confidence: 99%
“…The heat duty (eq ) measured in this work is defined as the heat required for the release of 1 mol of CO 2 , and it can be described by the ratio between the heat input and the amount of desorbed CO 2 using a widely accepted approach. , In this work, heat consumption for sorbent regeneration was reported as electricity consumption measured using a digital electric meter (Zhejiang Tepsung Electric Co., Ltd.) for the entire duration of the desorption process; this method, commonly used in laboratory-scale testing, allows for a reasonable comparison to evaluate the catalytic performance of different catalysts in a single work for each parallel test.…”
Section: Methodsmentioning
confidence: 99%